Pengaruh Kualitas Pelayanan Dan Brand Ambasador Terhadap Loyalitas Pengguna Aplikasi Shopee (Studi Kasus Mahasiswa FE UISU Jurusan Management Tahun Ajaran 2017) - Oddie Babudilla, Nilawati Nasti (Journal Economy and Currency Study (JECS), 2021)
This study was conducted to determine the effect of service quality and brand ambassador on Shopee Application User Loyalty (Case Study of FE UISU Student Management Department Academic Year 2017) as well as the results of the study. From the output above, it is known that the coefficient of determination (R Square) of 0.520 means 52 % Loyalty of shopee shopping customers can be explained by the variable Quality of service and Brand Ambassador while the remaining 48% is influenced by other variables that are not examined in this study. Based on the results of the analysis in this study, it can be concluded as follows: Product Quality (X1) has a positive and significant effect on Shopee Customer Loyalty, Brand Ambassador (X2) has a positive and significant impact on Shopee Customer Loyalty, Service Quality (X1) and Brand Ambassador (X2) simultaneously has a positive and significant influence on shopee customer loyalty